Differences in acoustic and perceptual parameters of the voice between elderly and young women at habitual and high intensity - Menezes, Keyla S. Mazzetto de; Master, Suely [UNESP]; Guzman, Marco; Bortnem, Cori; Ramos, Luiz Roberto (Elsevier B. V., 2014)
The present study aimed to compare elderly and young female voices in habitual and high intensity. The effect of increased intensity on the acoustic and perceptual parameters was assessed. Sound pressure level, fundamental frequency, jitter, shimmer, and harmonic to noise ratio were obtained at habitual and high intensity voice in a group of 30 elderly women and 30 young women. Perceptual assessment was also performed. Both groups demonstrated an increase in sound pressure level and fundamental frequency from habitual voice to high intensity voice. No differences were found between groups in any acoustic variables on samples recorded with habitual intensity level. No significant differences between groups were found in habitual intensity level for pitch, hoarseness, roughness, and breathiness. Asthenia and instability obtained significant higher values in elderly than young participants, whereas, the elderly demonstrated lower values for perceived tension and loudness than young subjects. Acoustic and perceptual measures do not demonstrate evident differences between elderly and young speakers in habitual intensity level. The parameters analyzed may lack the sensitivity necessary to detect differences in subjects with normal voices. Phonation with high intensity highlights differences between groups, especially in perceptual parameters. Therefore, high intensity should be included to compare elderly and young voice.

Introducción y objetivos el presente estudio tiene como propósito comparar las voces de los sujetos ancianos y jóvenes durante la fonación con intensidad habitual y alta. se evaluó el efecto del incremento de la intensidad en parámetros acústicos y perceptuales. métodos se obtuvieron los siguientes parámetros: nivel de presión del sonido, frecuencia fundamental, jitter, shimmer y el ratio armónico-ruido a intensidad habitual y alta en un grupo de 30 mujeres ancianas y 30 jóvenes. también se llevó a cabo un análisis perceptual de todas las muestras grabadas. resultados ambos grupos mostraron un incremento de spl y f0 al comparar la intensidad habitual con la alta. no se encontraron diferencias entre los grupos en ninguna variable acústica en las muestras grabadas con intensidad habitual. no se encontraron diferencias significativas entre ambos grupos con intensidad habitual para tono, ronquera, aspereza y voz soplada. la astenia e inestabilidad mostraron valores significativamente más altos en los sujetos ancianos que en los jóvenes, mientras que la percepción de tensión y sonoridad evidenció valores menores en los ancianos que en los jóvenes. conclusiones ninguna de las mediciones acústicas ni perceptuales mostraron diferencias evidentes entre ancianos y jóvenes con el nivel de intensidad habitual. los parámetros analizados podrían carecer de la sensibilidad necesaria para detectar diferencias en sujetos con voces normales. la fonación con niveles de intensidad alta acentúa las diferencias entre grupos, especialmente en los parámetros perceptuales. por lo tanto, la evaluación vocal a alta intensidad debería incluirse al comparar voces de ancianos y jóvenes.
Diferencias de los parámetros acústicos y perceptuales de la voz entre sujetos ancianos y jóvenes con intensidad habitual y alta
Keywords: Acústica del habla; Aging; Auditory perception; Cualidad vocal; Envejecimiento; Percepción auditiva; Speech acoustics; Voice quality; Envejecimiento; Cualidad vocal; Acústica del habla; Percepción auditiva